Dissemination of Surjan technology on rice cultivation in high-salt rice fields - Nasrudin Nasrudin; Siti Nurhidayah; Kusuma Agdhi Rahwana (Universitas Muhammadiyah Magelang, 2021)
Farmers abandoned a lot of land in Sucen Hamlet due to the low productivity of the agricultural land. High salt levels, tidal flooding, and strong east winds were among the challenges faced. Surjan system combined with the use of superior varieties is a solution to increase the resistance of rice plants to abiotic stresses and increase productivity. The purpose of this community service is to apply appropriate technology based on local wisdom to increase food availability in Pangandaran Regency during the COVID-19 pandemic. Socialization, discussion, direct practice, and evaluation are the methods used in this activity. According to the results of the dissemination, 40% of farmers produce 1-3 tons / ha, 54% produce 3-5 tons / ha, and 6% produce >5 tons / ha. The dissemination of surjan and the use of Banyuasin rice varieties can boost rice productivity and give it a fluffier texture. This program is extremely beneficial, as evidenced by the fact that 87 % intend to use the Surjan system in their rice cultivation activities. Furthermore, 83 % prefer Banyuasin rice to other rice varieties. Furthermore, during the COVID-19 pandemic, the high productivity of rice produced in this pilot demonstration plot was able to meet food needs.